The effect of a water polo game on the blood redox status of male water polo players - Petridis, L.; Jamurtas, A. Z.; Nikolaidis, M. G.; Veskousis, A.; Kouretas, D. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The purpose of this study was to examine the effects of a single water polo game on the blood redox status of male water polo players. Twelve male adult athletes (25.8±3.7 yrs) participated in the study and blood samples were taken before and after a water polo game of the Greek national championship. Mean playtime was 42.8 ± 9.4 min, which corresponded to 78.12±17.14% of the total playtime. Blood lactate concentration after the game reached considerably high values (9.16±3.91 mmol/L). Blood volume didn`t change after the game. Thiobarbituric acid-reactive substances (TBARS) increased significantly following the game (44%) whereas there was no difference in oxidized glutathione concentration (GSSG), protein carbonyls, catalase activity and total antioxidant capacity. Eventhough the results suggest that an intense exercise, like a water polo game, can induce blood oxidative stress, as it is indicated by the increase of TBARS, the absence of change in the other redox status indices measured in this study, indicate that further studies need to be done in this field to elaborate a possible connection between this type of activity and the redox status of the athletes.